Effect of chitosan–tungsten composite coating obtained by electrophoretic deposition on the corrosion resistance of Ni–Ti alloy in physiological medium - José Anderson Machado Oliveira; Thales Gomes Araujo; Josiane Dantas Costa; Arthur Filgueira de Almeida; Ana Regina Nascimento Campos; Renato Alexandre Costa de Santana (The Journal of Engineering and Exact Sciences)
Ni–Ti shape memory alloys (Nitinol) are suitable for biomedical applications such as orthodontic, orthopedic, and cardiovascular implants. However, to avoid local inflammatory processes, efforts are being made to functionalize the surface of the Ni–Ti alloy with bioactive materials. Chitosan-based composite coatings can be applied to improve the properties of Ni–Ti alloys due to their excellent properties, such as low toxicity, biocompatibility, biodegradability, and good film-forming ability. In this work, the chitosan–tungsten composite (Chit–W) was evaluated as a protective coating for Ni–Ti alloy in a physiological medium (Ringer's solution). The results of surface morphology and chemical composition (SEM and EDX) confirmed the formation of the composite coating formed by a chitosan matrix impregnated with tungsten oxide nanoparticles. Corrosion resistance results proved the efficiency of the composite coating, acting as a protective barrier between the surface of the substrate (Ni–Ti) and the corrosive environment. Therefore, the results point to a possible system candidate (Ni–Ti alloy coated with Chit–W composite) suitable for applications in orthopedic implants.